Challenges, Job Satisfiers, and Self-Care among Perinatal Nurses in the United States during the COVID-19 Pandemic. Issue 3 (May 2023) - Iobst, Stacey E.; Breman, Rachel Blankstein; Walker, Mark; Wysong, Grace; Best, Natasha; Edmonds, Joyce K.
Abstract: Purpose: To explore the perceived challenges, job satisfiers, and self-care of perinatal nurses in the United States during the COVID-19 pandemic. Study Design and Methods: In May of 2021, a cross-sectional survey was distributed online to members of the Association of Women's Health, Obstetric, and Neonatal Nurses and the National Association of Neonatal Nurses. We calculated descriptive statistics on respondent characteristics and applied conventional content analysis to free-text comments. Results: Perinatal nurses ( N = 297) responded to three open-ended questions on their perceived challenges, job satisfiers, and self-care. Frequently reported challenges included changing guidelines and policies ( n = 101, 34%), personal protective equipment as a barrier ( n = 73, 24.6%), and visitor restrictions ( n = 64, 21.5%). Frequently reported job satisfiers were provision of high-quality care ( n = 137, 46.1%) and visitor restrictions ( n = 77, 25.9%). Respondents reported using mental ( n = 152, 51.2%) and physical ( n = 145, 48.8%) self-care strategies and 12.8% ( n = 38) reported using no self-care strategies. Clinical Implications: The ability to provide high-quality care was reported as a leading job satisfier. Poor communication of consistent, evidence-based guidelines, lack of personal protective equipment, and inadequate unit staffing were leading challenges. Visitor restrictions were a challenge and a job satisfier, suggesting opportunities to better include visitors as support people. Most respondents reported engaging in one or more types of self-care outside of the hospital setting. Future research is needed to examine strategies for self-care among perinatal nurses when at work in the hospital setting. Abstract : Perinatal nurses, like other nurses in the United States and around the world, have faced many challenges in providing high quality nursing care during the COVID-19 pandemic. In this study, members of the Association of Women's Health, Obstetric, and Neonatal Nurses and the National Association of Neonatal Nurses participated in an online survey about their experiences during the pandemic. Ability to provide high-quality care was reported as a leading job satisfier, while poor communication of consistent, evidence-based guidelines, lack of personal protective equipment, and inadequate unit staffing were leading challenges. Visitor restrictions were a challenge and a job satisfier, suggesting opportunities to better include visitors as support people. This study adds important information about maternity nursing practice in the United States during the COVID-19 pandemic.